2013
DOI: 10.3357/asem.3601.2013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Gravitoinertial Force During Vection

Abstract: We conclude that the observed strong relationship between vection and perceived weight stems from the brain's attempt to reconcile the inputs from the different self-motion senses. The current findings have important implications for all simulated self-motions either in virtual reality or in vehicle simulators (particularly fixed-base flight and driving simulators).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Seno et al (2013b) reported that vection could induce gravito-inertial force. Upward and downward vection was found to modulate perceived body weight, i.e., upward vection increased and downward vection decreased perceived body weight.…”
Section: Resultsmentioning
confidence: 98%
“…Seno et al (2013b) reported that vection could induce gravito-inertial force. Upward and downward vection was found to modulate perceived body weight, i.e., upward vection increased and downward vection decreased perceived body weight.…”
Section: Resultsmentioning
confidence: 98%